A Study of Governance and Public Participation in Indonesian Megaprojects: A Comparative Analysis with International Practices - Rohman, Muhammad Syaifur (Jurnal Planologi, 2025)
This research analyzes governance and public participation in infrastructure megaprojects in Indonesia, such as MRT Jakarta and Trans-Java Toll Road, by comparing national and international practices. Megaprojects frequently face challenges in the form of cost overruns, schedule delays, social conflicts, and significant environmental impacts. This study aims to evaluate the effectiveness of implemented governance and public participation models, and compare them with international best practices. The study uses a literature approach and international case analysis to explore governance models, such as Public-Private Partnership (PPP) and more inclusive public participation approaches. The results show that transparent, accountable governance that involves communities from the outset can enhance public acceptance and project sustainability. Comparative analysis with international case studies provides insights into adapting best practices to the Indonesian context. Strategic recommendations include financing innovations, utilization of digital technology, and a holistic approach that considers social, economic, and environmental impacts.Keywords: Governance, Public Participation, Megaprojects, Infrastructure, Sustainability